FAKTOR YANG MEMPENGARUHI KEPUTUSAN NASABAH UNTUK MENABUNG PADA PT. BANK ACEH SYARIAH CABANG BIREUEN - Hamdani Hamdani (Ekonis: Jurnal Ekonomi dan Bisnis, 2022)
Abstract: This study aims to know the factors that influence the customers saving decisions partially and simultan cously on the dependent variable, namely the customer decision. This study uses the primary date sources, namely questionnaires purposive random sampling method. The questionnaire was distributed as many as 100 respondents at PT. Bank Aceh Syariah Branch Bireuen. To find out the factors that influence customer decisions among products (X1), services (X2), motivation (X3) and customer decision (Y), the multiple linear regression analysis method is used. From the analysis show that the product, service and motivation partially have a positive and significant effect on the customer’s decision in saving money at PT. Bank Aceh Syariah Branch Bireuen. In this study the most dominant variable in influencing the dependent variable is service (X2) and motivation (X3). PT. Bank Aceh Syariah Cabang Branch Bireuen must be able to maintain and improve product quality so that customers are interested in saving their money at PT. Bank Aceh Syariah Branch Bireuen.Keywords: Products, Services, Motivations and Customer Decisions